Isolation and molecular characterization of clinical and environmental dematiaceous fungi and relatives from Iran - Gholamreza Shokoohi; Hamid Badali; Bahram Ahmadi; Kazuo Satoh; Sadegh Nouripour-Sisakht; Mahnaz Nikaeen; Mohsen Geramishoar; Nilufar Jalalizand; Sahar Kianipour; Hossein Mirhendi; Koichi Makimura (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: The frequency and genetic diversity of black fungi in environmental and clinical settings have not been fully studied in Iran. This study aimed to identify and evaluate intra- and inter-species DNA sequence variation and also understand the phylogenetic relationships of melanized fungi and relatives isolated from different geographical regions of Iran.Materials and Methods: In total, 111 clinical and environmental strains of dematiaceous fungi were isolated, and their internal transcribed spacer ribosomal DNA(rDNA) regions were sequenced and analyzed.Results: An inter-species nucleotide sequence diversity rate of 1 to 464 nucleotides was observed between the species. Intra-species differences were found in the strains of Alternaria alternata, Cladosporium cladosporioides, Alternaria tenuissima, Curvularia spicifera, Aureobasidium pullulans, Curvularia hawaiiensis, Neoscytalidium dimidiatum,Alternaria terricola, Alternaria chlamydospora, Didymella glomerata, and Drechslera dematioidea by 0-59, 0-22, 0-4, 0-4, 0-3, 0-2, 0-2, 0-2, 0-2, 0-1, and 0-1 nt, respectively.Conclusion: The internal transcribed spacer rDNA is useful for the discrimination of several taxa of dematiaceous fungi. However, a better understanding of the taxonomy of species of Alternaria requires a larger rDNA region or a library of other gene sequences.